THE USE OF QUIZIZZ TO IMPROVE MOTIVATION AND LEARNING OUTCOMES OF PHOTOSYNTHESIS IN GRADE IV STUDENTS OF UPT SDN 70 GRESIK - Syifa, Faiza Mahali (Universitas Muhammadiyah Lamongan, 2024)
Abstract: This research was started from the learning outcomes of students in class IV UPT SDN 70 Gresik which were below the Average Minimum Completeness Criteria (KKM). This research investigates students' understanding of the IPAS subject material about photosynthesis of green plants and the stages of light reactions and dark reactions during photosynthesis. This research is intended for students in the class. The method used was Classroom Action Research (PTK). The data analysis technique used is descriptive qualitative while the data collection process through student worksheets, student learning outcomes and documentation in the form of photos. From the results of data analysis, the research showed significant changes. This is proven by the increase in learning results and pleasant student learning motivation. The application of Quizizz media helps students understand the material well. It can be seen from the results of cycle I the average score was 68.69 with a percentage of 68.7% while in cycle II it increased to 79.78 with a percentage of 79.8%. From the results of the research that has been done, it can be concluded that the use of Quizizz to increase Motivation and Learning Results of Photosynthesis in Class IV Students at UPT SDN 70 Gresik has gone well so that student learning outcomes and motivation increase and the score target exceeds the KKM. Keywords: The Application of Quizizz, Learning Motivation, Learning Outcomes, Photocytesis